Switched adaptive observers design for a class of switched uncertain nonlinear systems. (May 2020) - Liu, Qian; Zhao, Jun
Abstract: In this paper, a switched adaptive observer for a class of switched uncertain nonlinear systems is designed by using an average dwell time (ADT) method. Due to that switching unknown parameters lead to different coordinates transformation for different subsystems, some new dwell-time conditions are provided by an improved ADT method. Also, the boundedness of all signals is ensured by a well defined persistent excitation condition under a class of switching signals with ADT. Finally, the effectiveness of the theoretical results in this paper is demonstrated through a simulation example.